Clinical parameters for the prediction of occult lymph node metastasis in patients with negative PSMA-PET - Huebner, Nicolai A; Wasinger, Gabriel; Rajwa, Pawel; Resch, Irene; Korn, Stephan; Rasul, Sazan; Baltzer, Pascal; Prüger, Larissa; Rauschmeier, Andreas; Seitz, Christian; Comperat, Eva; Shariat, Shahrokh F; et al. (Urologic oncology, 2024)
BACKGROUND: Depending on the risk of LN metastasis ePLND at RP is recommended. As ePLND has potential side effects, and diagnostics have improved substantially, our objective was to evaluate the performance of the Briganti 2019 nomogram in a contemporary cohort with preoperative negative PSMA-PET. METHODS: Patients with intermediate- and high-risk prostate cancer (CaP), undergoing RP and ePND at our center with preoperative negative [68Ga]Ga-PSMA-11 PET were included. The Accuracy of the nomogram was assessed using ROC analysis. The association of clinical parameters with the presence of LN metastasis was assessed using logistic regression. Specimen of prostate and LNs in patients with false negative PSMA-PET were additionally stained for AR and PSMA expression and assessed by IHC. RESULTS: The study included 108 patients, 28% intermediate- and 72% high-risk. Twelve patients harbored occult LN metastasis. Accuracy of the nomogram was 0.62. [68Ga]Ga-PSMA-11 PET showed a NPV of 89%. IHC showed expression of PSMA and AR in the primary and LN metastasis in all patients. On logistic regression analysis only DRE (OR 2.72; 95%CI 1.01-7.35; P = 0.05) and percentage of cores with significant CaP (OR 1.29; 95%CI 1.05-1.60; P = 0.02) showed a significant association with LN metastasis. CONCLUSION: The currently used nomogram is suboptimal in detecting patients with occult LNM. While the cut-off value to perform ePLND can be increased slightly following a negative PSMA-PET scan, more accurate methods of identifying these patients are needed. Whether ePLND can have a therapeutic benefit, as opposed to a diagnostic only, needs to be re-evaluated in the PSMA-PET era.
Keywords: nádory prostaty; lymfatické metastázy; lymfadenektomie; lidé; Lymphatic Metastasis; Lymph Nodes; lymfatické uzliny; Male; Gallium Radioisotopes; PET/CT; Prostatic Neoplasms; Lymph Node Excision; radioizotopy galia; Humans; Positron Emission Tomography Computed Tomography; mužské pohlaví